Warm realism in Chinese microdramas: A term frequency analysis of audience comments on The Puppy Laifu - Yuan Tian; Pan Cheng (PLoS ONE, 2026)
Starting from the connotation of warm realism, this study analyzes the narrative characteristics of the warm realist microdrama The Puppy Laifu on the Douyin platform. The audience’s comments on the drama are selected as the research object. Narratology is also introduced into the short drama for category construction. On the basis of a combination of audience reception theory and word frequency analysis, a “narrative-decoding” analytical framework is constructed to study the narrative setup and audience reception mechanism. The analysis reveals that the emotional resonance of the audience is centered on the active decoding of characters’ morality and competence, a strong critique of the characters’ words and actions, and a scrutiny of the rationality of the plot settings within the story experience. Therefore, narrative designs incorporating moral dilemmas and emotional disparities can significantly increase the willingness to comment. To synergistically amplify overall interaction effectiveness and improve dissemination outcomes, platforms should focus on maximizing audience’ willingness to comment because of the strong positive correlation among four indicators: comments, likes, favorites, and shares. To improve the creation and dissemination of warm realistic microdramas, creators should consider the following suggestions: the use of flat characters to create moral conflict; the establishment of emotional resonance through deliberate emotional contrasts at the plot level; conflict resolution to provide emotional solace; and strengthening of the mechanisms likely to trigger comments.